Late-Term Elective Abortion and Susceptibility to Posttraumatic Stress Symptoms - Priscilla K. Coleman; Catherine T. Coyle; Vincent M. Rue (Hindawi Limited, 2010)
The primary aim of this study was to compare the experience of an early abortion (1st trimester) to a late abortion (2nd and 3rd trimester) relative to Posttraumatic Stress Disorder (PTSD) symptoms after controlling for socio-demographic and personal history variables. Online surveys were completed by 374 women who experienced either a 1st trimester abortion (up to 12 weeks gestation) or a 2nd or 3rd trimester abortion (13 weeks gestation or beyond). Most respondents (81%) were U.S. citizens. Later abortions were associated with higher Intrusion subscale scores and with a greater likelihood of reporting disturbing dreams, reliving of the abortion, and trouble falling asleep. Reporting the pregnancy was desired by one's partner, experiencing pressure to abort, having left the partner prior to the abortion, not disclosing the abortion to the partner, and physical health concerns were more common among women who received later abortions. Social reasons for the abortion were linked with significantly higher PTSD total and subscale scores for the full sample. Women who postpone their abortions may need more active professional intervention before securing an abortion based on the increased risks identified herein. More research with diverse samples employing additional measures of mental illness is needed.